(untitled) (Modern American Journal of Social Sciences and Humanities, 2026)
The article covers the history of the Khoja Abdulaziz or Azizboy madrasah in the city of Karshi, its architectural and planning structure, features, the state of preservation of the monument, engineering geological, geodetic, archaeological research conducted during the renovation of the building, and analyses of the conservation and restoration of the monument.